2015
DOI: 10.4018/ijissc.2015100101
|View full text |Cite
|
Sign up to set email alerts
|

Nobody Knows You're a Dog but Everybody Knows You're a Republican

Abstract: Geography often serves as at least a partial determinant of economic and cultural characteristics. For example, individuals who live in affluent neighborhoods are likely to come into contact with other individuals who have similar income and education levels, which often tend to be associated with political views and personal interests. However, within electronic social networks (ESNs), geographical barriers weaken or disappear; interacting with someone from another country is as easy as interacting with someo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In addition to sharing their religious faith, people use social media to share information about their favorite religious organizations, activities, preachers, religious resources, Web sites, educational materials, new issues, and much more (Groenpj, 2011). Some experts believe social networks are more successful than traditional, offline forms of communication in spreading new viewpoints including religious believe (Balint & Gustafson, 2015). Preston (2011) reported that although it is too early to say that social media has transformed the way in which people practice religion, the number of people discussing faith on Facebook has significantly increased in the past year.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to sharing their religious faith, people use social media to share information about their favorite religious organizations, activities, preachers, religious resources, Web sites, educational materials, new issues, and much more (Groenpj, 2011). Some experts believe social networks are more successful than traditional, offline forms of communication in spreading new viewpoints including religious believe (Balint & Gustafson, 2015). Preston (2011) reported that although it is too early to say that social media has transformed the way in which people practice religion, the number of people discussing faith on Facebook has significantly increased in the past year.…”
Section: Literature Reviewmentioning
confidence: 99%